Production and Reliability Oriented SOFC Cell and Stack Design. (30th May 2017) - Hauth, Martin; Lawlor, Vincent; Cartellieri, Peter; Zechmeister, Christopher; Wolff, Sebastian; Bucher, Christian; Malzbender, Jürgen; Wei, Jianping; Weber, André; Tsotridis, Georgios; Frandsen, Henrik Lund; Kwok, Kawai; et al.
Abstract : The paper presents an innovative development methodology for a production and reliability oriented SOFC cell and stack design aiming at improving the stacks robustness, manufacturability, efficiency and cost. Multi-physics models allowed a probabilistic approach to consider statistical variations in production, material and operating parameters for the optimization phase. A methodology for 3D description of spatial distribution of material properties based on a random field models was developed and validated by experiments. Homogenized material models on multiple levels of the SOFC stack were established. The probabilistic models were related to the experimentally obtained properties of base materials to establish a statistical relationship between the material properties and the most relevant load effects. Software algorithms for meta models that allow the detection of relationships between input and output parameters and to perform a sensitivity analysis were developed and implemented. The capabilities of the methodology is illustrated on two practical cases.